Perancangan dan Pembuatan Aplikasi Pembelajaran Tata Surya untuk Anak SMP Berbasis Android - Hady, Irawan; Andjarwirawan, Justinus; Rostianingsih, Silvia (Jurnal Infra, 2015)
Learning is a concept that reflects the learning process. Solar System is a collection of celestial objects which consists of a massive star called the sun, and all objects that surround it the objects are planets, satellites, asteroids, comets and meteors.Technology in learning has changed the way learning is different from the traditional learning process conducted by face-to-face interaction between teachers and students, so that technology in learning is defined as a medium for distributing information. Learning application can help the learning process to be innovative, interesting, and more interactive. In addition the process of learning can be done anywhere and anytime, and can increase student interest.